Explaining Risk Premium on Bank Bonds by Financial Ratios - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
This paper examines the relationship between the risk premium on bank bonds and banks' financial ratios. It also tries to show that bonds issued by banks with strong fundamentals offer less premium as they are perceived to be less risky by investors. Components of CAMELS rating methodology are used to establish the link between a bank's financial ratios and the risk premium on their bonds. Financial ratios of 11 Turkish banks, which issued bonds between the years 2012 and 2016, are calculated. This study investigates the links between bond premiums and financial ratios with k-means cluster and discriminant analysis. It also shows the importance of fundamentals on the level of risk premium paid to bond investors by banks.
Keywords: Bank bonds; Bond risk premium; CAMELS ratings; Financial ratios; Turkish banks